Circular Economy Approach to Waste Governance and Disaster-Resilient Villages (Destana): A Case Study of Pijot Village, Keruak Subdistrict - Lalu Nova Saza Yusma; Hilmiyatun H (Yayasan Daarul Huda Kruengmane, 2026)
This community service program aims to enhance the awareness and capacity of the residents of Pijot Village, Keruak Subdistrict, East Lombok Regency, in managing household waste and strengthening the capacity of a Disaster-Resilient Village (Desa Tangguh Bencana/Destana). The approach employed is the circular economy, based on the principles of reduce, reuse, and recycle (3R), combined with the Participatory Rural Appraisal (PRA) method. The main activities include awareness campaigns on the hazards of waste, the distribution of 14 waste bins across eight hamlets, training on waste segregation, disaster mitigation simulations, and community assistance. The results indicate increased public awareness of the dangers of waste, the establishment of waste collection points, and the utilization of agricultural waste (tobacco residues) as organic compost. The program also supports village ecotourism by maintaining environmental cleanliness. The novelty of this program lies in the integration of waste governance, disaster mitigation, and ecotourism-based productive economy within a circular economy framework.